A System of Generalized Variational-Hemivariational Inequalities with Set-Valued Mappings - Zhi-bin Liu; Jian-hong Gou; Yi-bin Xiao; Xue-song Li (Journal of Applied Mathematics)
By using surjectivity theorem of pseudomonotone and coercive operators rather than the KKM theorem and fixed point theorem used in recent literatures, we obtain some conditions under which a system of generalized variational-hemivariational inequalities concerning set-valued mappings, which includes as special cases many problems of hemivariational inequalities studied in recent literatures, is solvable. As an application, we prove an existence theorem of solutions for a system of generalized variational-hemivariational inequalities involving integrals of Clarke's generalized directional derivatives.